Dynamics of ecological soil parameters in the process of vegetation of oak forests’ restoration of polissia of Ukraine - Ivanyuk , I.D.; Ivanyuk , T.M. (Forestry, Forest, Paper and Woodworking Industry, 2018)
A study was conducted to establish the dynamics of ecological parameters of soil by phytoindicationmethod on the basis of complete geobotanical descriptions in oak plantations of wet forest conditions of Polissia. The research analyzed the dynamics of: soil moisture (Hd; soil moisture regime (fH); soil acidity amplitudes (Rc); amplitudes of the amount of calcium carbonates (Ca) and magnesium (Mg); the amount of mineral nitrogen (Nt); soil aeration (Ae). It is established that after continuous fellings the indicators of soil parameters change both in the direction of increase and in the direction of decrease. The main reason for this is probably the removal of the edification layer - the stand, which is characterizedby a significant absorption capacity. During the process of stands’ growth, with age, there is a clear tendency to return the level of soil indicators to the original values ​​that are characteristic of mature subclimax oak plantations.Thisprocessinoak plantations begins after the closure of the crowns and the formation of their own canopy.Most soil indicators in points were characterized by a narrow range of values. In general, the obtained data on phytoindication of ecological parameters of habitats indicate the presence of a clear trend in wet soil conditions of Polissia after continuous fellings in the process of restoring the biodiversity of oak plantations.